THE CURRENT STATE OF DEVELOPMENT OF MATHEMATICAL IMAGINATION OF CHILDREN IN PREPARATORY GROUPS OF PRESCHOOL EDUCATIONAL ORGANIZATIONS (Scientific journal of the Fergana State University, 2024)
This article describes the current state of development of the mathematical imagination of children in preparatory groups of preschool educational organizations.